Arctic shipping insurance : towards a harmonisation of practices and costs? - Sarrabezolles, Aurélie; Lasserre, Frédéric; Hagouagn’rin, Zebret (Polar Record, 2016)
Insurance is an important component of shipping costs, albeit minor when compared to capital, crew or fuel. If the literature of Arctic shipping agrees that insurance premiums are likely to be higher for Arctic shipping, no study so far has tried to assess the cost of Arctic shipping insurance premiums, nor what specific demands insurance firms might formulate before agreeing to give coverage to a shipping company, thus presenting obstacles to entry in the Arctic shipping market. We first present insurance policies and costs as they are discussed in the literature on Arctic shipping. We also sketch out how their risk-assessment process was influenced by the IMO (International Maritime Organization) and classification societies. Then we outline the results of a survey conducted between 2012 and 2013 with insurance firms on their Arctic shipping policies.